Carbon-cured red mud-regenerated micro powder core-shell type ceramsite adsorbent as well as preparation method and application thereof

By using carbon-curing red mud-regenerated micro powder core-shell type ceramic adsorbent in the preparation of ceramic adsorbent, the problem of resource utilization of red mud, regenerated micro powder and municipal sludge is solved, the performance and stability of ceramic adsorbents are improved, and the preparation of low-carbon and environmentally friendly ceramic adsorbents is achieved.

CN119657076AActive Publication Date: 2025-03-21GUANGXI UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411597251.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-21
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize red mud, regenerated micro powder and municipal sludge, which leads to the pollution of the environment during the storage process, and the preparation of ceramic adsorbents has problems of unstable performance and waste of resources.

Method used

The preparation method of carbon-cured red mud-regenerated micro powder core-shell ceramic adsorbent is adopted. The core-shell ceramic adsorbent is prepared by synergistically using sludge biochar, red mud and regenerated micro powder. The sludge biochar is used as the skeleton to reduce the quality of the ceramic and improve the adsorption performance. At the same time, the alkalinity of the red mud and solidify heavy metals are neutralized by shell materials to improve stability and safety.

Benefits of technology

The coordinated disposal of red mud, recycled micro powder and municipal sludge has been achieved, which significantly improves the adsorption performance and stability of ceramic adsorbents, reduces dependence on natural resources and production costs, and reduces environmental pollution and carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657076A_ABST
    Figure CN119657076A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-cured red mud-regenerated micro-powder core-shell type ceramsite adsorbent as well as a preparation method and application of the carbon-cured red mud-regenerated micro-powder core-shell type ceramsite adsorbent. The adsorbent comprises the following components in parts by weight: 60-100 parts of sludge biochar, 30-60 parts of red mud, 50-80 parts of regenerated micro powder, 10-20 parts of water, 2-5 parts of a pore forming agent, 0-5 parts of an activating agent and 1-3 parts of a chelating agent, the preparation method comprises the following steps: B1, mixing the red mud, the regenerated micro powder and the pore-forming agent, adding the sludge biochar, and continuously and uniformly mixing; b2, dissolving an activating agent and a chelating agent; b3, spraying the solution, granulating, and screening to obtain ceramsite raw pellets with the particle size of 5-10mm; b4, performing carbon maintenance on the ceramsite raw pellets for 1 day; and B5, placing the cured particles in water, and curing for 3-28 days to obtain the carbon cured red mud-regenerated micro powder core-shell type ceramsite adsorbent. The ceramsite has the characteristics of low carbon, light weight and high adsorption, meanwhile, wastes are effectively utilized, and the environmental pollution is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorbent preparation, and in particular to a carbon-cured red mud-regenerated micro-powder core-shell ceramsite adsorbent and a preparation method and application thereof. Background Art

[0002] Red mud, recycled micron and municipal sludge are three types of solid waste generated in urban and industrial development.

[0003] Red mud is solid waste generated in the process of producing alumina from bauxite. Its main components include alumina, iron oxide, silicon dioxide and alkaline oxides such as sodium and potassium. Due to its high alkalinity and heavy metal content, red mud is prone to cause serious environmental pollution during storage. Its storage not only occupies land, but also easily pollutes the environment. With the rapid development of cities and industries around the world, the output of municipal sludge and red mud will continue to increase, and effective resource utilization methods are urgently needed.

[0004] Recycled micro powder is a fine powder material obtained by crushing and screening construction waste. Its main components include cement hydration products, unhydrated cement particles, aggregate particles and old mortar wrapped in them. With the acceleration of urbanization, a large amount of construction waste is continuously generated. The traditional treatment method is mainly landfill or simple stacking, which not only wastes a lot of renewable resources, but also causes environmental pollution and waste of resources. Therefore, improving the utilization rate of recycled micro powder has become an important issue in the current construction industry.

[0005] Municipal sludge contains a large amount of organic matter, pathogens, heavy metals and other components. If these components are discharged directly without proper treatment, they will cause serious pollution to the environment, such as heavy metal pollution of soil and water sources, and damage to the ecosystem. As an effective sludge disposal method, sludge biochar can transform sludge through a high-temperature pyrolysis process, reduce the volume and stabilize heavy metals. It has high adsorption and can be used as an adsorbent to remove pollutants in water. However, unmodified sludge biochar may still release heavy metals, posing a potential threat to the environment, so it needs to be properly modified to enhance stability and adsorption performance.

[0006] As an adsorbent, ceramsite is widely used in the process of water purification, and its adsorption characteristics are similar to those of sludge biochar. In the preparation of ceramsite, the application of red mud and regenerated micropowder in ceramsite has also been explored, but there are still many deficiencies in their respective use in ceramsite. Due to its high alkalinity and heavy metal content, red mud is prone to unstable product performance in the application of ceramsite. The complex composition and poor stability of regenerated micropowder also bring challenges to the preparation of ceramsite.

[0007] The present invention combines red mud, regenerated micropowder and sludge biochar to synergistically prepare ceramsite adsorbent, which has significant advantages. First, sludge biochar has the advantages of light weight and high adsorption, and can be used as a skeleton to reduce the mass of ceramsite while improving the adsorption performance of ceramsite. Secondly, the synergistic preparation of shell materials by red mud and regenerated micropowder can effectively neutralize the alkalinity of red mud and improve the stability and safety of shell materials. At the same time, the shell material can solidify the heavy metals in red mud and sludge biochar, reducing pollution to the environment. In addition, using these solid wastes as raw materials can not only reduce dependence on natural resources and reduce production costs, but also bring economic benefits.

[0008] Therefore, it is very necessary to develop a new, low-carbon, economical ceramsite adsorbent and its preparation method. Summary of the invention

[0009] The purpose of the present invention is to provide a carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent and a preparation method thereof, so as to achieve the coordinated disposal of red mud, regenerated micropowder and municipal sludge, and at the same time obtain a core-shell ceramsite adsorbent with good adsorption performance.

[0010] In order to achieve the above purpose, the present invention adopts the following technical means:

[0011] A carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent, whose raw materials include the following components in parts by weight: 60-100 parts of sludge biochar, 30-60 parts of red mud, 50-80 parts of regenerated micropowder, 10-20 parts of water, 2-5 parts of pore-forming agent, 0-5 parts of activator, and 1-3 parts of chelating agent.

[0012] Furthermore, the sludge biochar is prepared from municipal sludge, and the preparation method thereof comprises the following steps:

[0013] Step A1: Place the filter press sludge cake after removing a large amount of water through the filter press in a drying oven, dry at 105°C for 24 hours, and after preliminary crushing by a crusher, pass through a 150-mesh sieve to obtain dry sludge;

[0014] Step A2: Put the dry sludge into a granulator, add an appropriate amount of water, prepare sludge balls with a diameter of 1 cm, put them into a drying oven at 50°C for 5 hours, and obtain sludge balls;

[0015] Step A3: placing the sludge balls in a high-temperature tube furnace, controlling the heating rate to 5°C / min, pyrolyzing at 400-600°C for 0.5-2h under a nitrogen atmosphere, then stopping heating and cooling to room temperature to initially form biochar;

[0016] Step A4: The biochar is repeatedly washed with deionized water to remove soluble impurities, and then dried at 105° C. for 6-10 h to obtain sludge biochar.

[0017] Furthermore, the average particle size of the red mud and the regenerated micropowder is 10-20 μm, wherein the activity index of the regenerated micropowder is greater than 0.7.

[0018] Furthermore, the pore-forming agent is aluminum powder with a particle size of 0.5-2.0 μm.

[0019] Furthermore, the activator is prepared by mixing water glass and sodium hydroxide, and the mass ratio thereof is 10-15:1.

[0020] Furthermore, the chelating agent is prepared by mixing sodium hexametaphosphate and sodium polyacrylate, and the mass ratio thereof is 1:1.

[0021] The present invention also provides a method for preparing the carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent, comprising the following steps:

[0022] B1: Red mud, regenerated micropowder and pore-forming agent were placed in a granulator and mixed for 2-4 minutes, then sludge biochar was added, and the granulator was operated for 2 minutes to fully mix and obtain a mixture;

[0023] B2: Divide the water into two parts, dissolve the activator and the chelating agent in different water respectively to obtain two additive solutions;

[0024] B3: Continuously spray two additive solutions for granulation to obtain spherical particles, and then screen to obtain ceramsite raw material balls with a particle size of 5-10 mm; the rotation speed of the granulator is 30-40rpm, and the granulation is continuous for 6-12min, during which the additive solution is evenly sprayed, and then it is continued to run for 1-3min after the end to compact the particles;

[0025] B4: Carbide-cured raw material balls for 1 day; the carbon curing conditions are: temperature of 25±2°C, humidity of 50%±2%, CO2 concentration of 20%±2%-40%±2%;

[0026] B5: placing the carbon-cured particles in water and curing them for 3-28 days to obtain carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent; the curing conditions are: temperature of 25±2° C. and humidity of more than 90%.

[0027] The carbon-cured red mud-regenerated micro-powder core-shell ceramsite adsorbent described in the present invention can be used to remove Pb from water. 2+ , Cu 2+ or PO4 2- At room temperature, the carbon-cured red mud-regenerated micro-powder core-shell ceramsite adsorbent is added at a mass ratio of 1:20 between the carbon-cured red mud-regenerated micro-powder core-shell ceramsite adsorbent and water.

[0028] The present invention has the following beneficial effects:

[0029] 1. The present invention uses red mud, recycled micropowder and municipal sludge as the main raw materials, which significantly reduces the use of cement and the dependence on natural resources. Red mud, recycled micropowder and municipal sludge are all solid wastes. This method not only effectively reduces the pollution of industrial waste and construction waste to the environment; at the same time, the use of a carbon curing process without burning not only reduces carbon emissions during the sintering process compared to sintered ceramsite, but also absorbs CO2, which is in line with the green and low-carbon environmental protection concept.

[0030] 2. During the preparation process, the shell material wraps the sludge biochar, reducing the heavy metal leaching of the sludge biochar. At the same time, sodium hexametaphosphate and sodium polyacrylate are used to play the dual role of chelating agent and water reducer. While optimizing the fluidity, it further ensures the stability of heavy metal solidification and prevents its migration and release in the environment, thereby improving the safety performance and environmental benefits of the expanded clay adsorbent.

[0031] 3. Sludge biochar has a rough and porous surface and contains clay minerals in red mud, so both exhibit good adsorption performance. In the preparation process of ceramsite, in order to maintain the porous characteristics of ceramsite and compensate for the possible cavitation blockage of sludge biochar, pore-forming agents are added to the shell material. This ceramsite prepared from red mud not only has excellent adsorption and solidification capabilities, but also further enhances the market competitiveness of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The present invention is a flow chart of a method for preparing a carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent. DETAILED DESCRIPTION

[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] A carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent includes the following components in parts by weight: 70 parts of sludge biochar, 35 parts of red mud, 60 parts of regenerated micropowder, 18 parts of water, 3 parts of pore formers, 4 parts of activators, and 1 part of chelating agents. The average particle size of the red mud and the regenerated micropowder is 10 μm, wherein the activity index of the regenerated micropowder is 0.85. The pore former is aluminum powder with a particle size of 0.5-2.0 μm. The activator is prepared by mixing water glass and sodium hydroxide, and the mass ratio thereof is 10:1. The chelating agent is prepared by mixing sodium hexametaphosphate and sodium polyacrylate, and the mass ratio thereof is 1:1.

[0036] The sludge biochar is prepared from municipal sludge, and the preparation method thereof comprises the following steps:

[0037] Step A1: Place the filter press sludge cake after removing a large amount of water through the filter press in a drying oven, dry at 105°C for 24 hours, and after preliminary crushing by a crusher, pass through a 150-mesh sieve to obtain dry sludge;

[0038] Step A2: Put the dry sludge into a granulator, add an appropriate amount of water, prepare sludge balls with a diameter of 1 cm, put them into a drying oven at 50°C for 5 hours, and obtain sludge balls;

[0039] Step A3: placing the sludge balls in a high-temperature tube furnace, controlling the heating rate to 5°C / min, pyrolyzing at 600°C for 1 hour under a nitrogen atmosphere, stopping heating, cooling to room temperature, and initially forming biochar;

[0040] Step A4: The biochar was repeatedly washed with deionized water to remove soluble impurities, and then dried at 105° C. for 10 h to obtain sludge biochar.

[0041] The preparation method of the carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent is prepared in the following manner:

[0042] B1: Red mud, regenerated micropowder and pore-forming agent were placed in a granulator and mixed for 3 min, then sludge biochar was added, and the granulator was operated for 2 min to fully mix and obtain a mixture;

[0043] B2: Divide the water into two parts, dissolve the activator and the chelating agent in different parts of water respectively, and obtain two additive solutions;

[0044] B3: Continuously spray two additive solutions for granulation to obtain spherical particles, and then screen to obtain ceramsite raw material balls with a particle size of 5-10 mm; during granulation, the speed of the granulator is 35 rpm, and the granulation is continuous for 9 minutes, during which the additive solution is evenly sprayed, and then it is continued to run for 3 minutes to compact the particles;

[0045] B4: The raw material balls are carbon cured for 1 day; the carbon curing conditions are: temperature 25±2℃, humidity 50%±2%, CO2 concentration 30%±2%;

[0046] B5: The cured particles are placed in water and cured for 28 days. The curing conditions are: temperature is 25±2°C, humidity is above 90%, and carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent is obtained.

[0047] Example 2

[0048] A carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent includes the following components in parts by weight: 80 parts of sludge biochar, 30 parts of red mud, 80 parts of regenerated micropowder, 20 parts of water, 5 parts of pore formers, 5 parts of activators, and 2 parts of chelating agents. The average particle size of the red mud and the regenerated micropowder is 12 μm, wherein the activity index of the regenerated micropowder is 0.8. The pore former is aluminum powder with a particle size of 0.5-2.0 μm. The activator is prepared by mixing water glass and sodium hydroxide, and the mass ratio thereof is 12:1. The chelating agent is prepared by mixing sodium hexametaphosphate and sodium polyacrylate, and the mass ratio thereof is 1:1.

[0049] The sludge biochar is prepared from municipal sludge, and the preparation method thereof comprises the following steps:

[0050] Step A1: Place the filter press sludge cake after removing a large amount of water through the filter press in a drying oven, dry at 105°C for 24 hours, and after preliminary crushing by a crusher, pass through a 150-mesh sieve to obtain dry sludge;

[0051] Step A2: Put the dry sludge into a granulator, add an appropriate amount of water, prepare sludge balls with a diameter of 1 cm, put them into a drying oven at 50°C for 5 hours, and obtain sludge balls;

[0052] Step A3: placing the sludge balls in a high-temperature tube furnace, controlling the heating rate to 5°C / min, pyrolyzing at 500°C for 2h under a nitrogen atmosphere, stopping heating, cooling to room temperature, and initially forming biochar;

[0053] Step A4: The biochar was repeatedly washed with deionized water to remove soluble impurities, and then dried at 105° C. for 9 h to obtain sludge biochar.

[0054] The preparation method of the carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent is prepared in the following manner:

[0055] B1: Red mud, regenerated micropowder and pore-forming agent were placed in a granulator and mixed for 2 min, then sludge biochar was added, and the granulator was operated for 2 min to fully mix and obtain a mixture;

[0056] B2: Divide the water into two parts, dissolve the activator and the chelating agent in different water respectively to obtain two additive solutions;

[0057] B3: Continuously spray two additive solutions for granulation to obtain spherical particles, which are then sieved to obtain ceramsite raw material balls with a particle size of 5-10 mm; during granulation, the speed of the granulator is 40 rpm, and the granulation is continuous for 7 minutes, during which the additive solution is evenly sprayed, and then the operation is continued for 1 minute to compact the particles;

[0058] B4: The raw material balls are carbon cured for 1 day; the carbon curing conditions are: temperature 25±2℃, humidity 50%±2%, CO2 concentration 40%±2%;

[0059] B5: The cured particles are placed in water and cured for 28 days. The curing conditions are: temperature is 25±2°C, humidity is above 90%, and carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent is obtained.

[0060] Example 3

[0061] A carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent includes the following components in parts by weight: 60 parts of sludge biochar, 45 parts of red mud, 65 parts of regenerated micropowder, 18 parts of water, 4 parts of pore formers, 3 parts of activators, and 3 parts of chelating agents. The average particle size of the red mud and the regenerated micropowder is 16 μm, wherein the activity index of the regenerated micropowder is 0.78. The pore former is aluminum powder with a particle size of 0.5-2.0 μm. The activator is prepared by mixing water glass and sodium hydroxide, and the mass ratio thereof is 15:1. The chelating agent is prepared by mixing sodium hexametaphosphate and sodium polyacrylate, and the mass ratio thereof is 1:1.

[0062] The sludge biochar is prepared from municipal sludge, and the preparation method thereof comprises the following steps:

[0063] Step A1: Place the filter press sludge cake after removing a large amount of water through the filter press in a drying oven, dry at 105°C for 24 hours, and after preliminary crushing by a crusher, pass through a 150-mesh sieve to obtain dry sludge;

[0064] Step A2: Put the dry sludge into a granulator, add an appropriate amount of water, prepare sludge balls with a diameter of 1 cm, put them into a drying oven at 50°C for 5 hours, and obtain sludge balls;

[0065] Step A3: placing the sludge balls in a high-temperature tube furnace, controlling the heating rate to 5°C / min, pyrolyzing at 500°C for 1 hour under a nitrogen atmosphere, stopping heating, cooling to room temperature, and initially forming biochar;

[0066] Step A4: The biochar was repeatedly washed with deionized water to remove soluble impurities, and then dried at 105° C. for 8 h to obtain sludge biochar.

[0067] The preparation method of the carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent is prepared in the following manner:

[0068] B1: Red mud, regenerated micropowder and pore-forming agent were placed in a granulator and mixed for 3 min, then sludge biochar was added, and the granulator was operated for 2 min to fully mix and obtain a mixture;

[0069] B2: Divide the water into two parts, dissolve the activator and the chelating agent in different water respectively to obtain two additive solutions;

[0070] B3: Continuously spray two additive solutions for granulation to obtain spherical particles, which are then sieved to obtain ceramsite raw material balls with a particle size of 5-10 mm; during granulation, the speed of the granulator is 40 rpm, and the granulation is continuous for 8 minutes, during which the additive solution is evenly sprayed, and then the operation is continued for 2 minutes to compact the particles;

[0071] B4: The raw material balls are carbon cured for 1 day; the carbon curing conditions are: temperature 25±2℃, humidity 50%±2%, CO2 concentration 40%±2%;

[0072] B5: The cured particles are placed in water and cured for 28 days. The curing conditions are: temperature is 25±2°C, humidity is above 90%, and carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent is obtained.

[0073] Example 4

[0074] A carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent includes the following components in parts by weight: 100 parts of sludge biochar, 60 parts of red mud, 50 parts of regenerated micropowder, 10 parts of water, 2 parts of pore formers, 1 part of activators, and 3 parts of chelating agents. The average particle size of the red mud and the regenerated micropowder is 10 μm, wherein the activity index of the regenerated micropowder is 0.75. The pore former is aluminum powder with a particle size of 0.5-2.0 μm. The activator is prepared by mixing water glass and sodium hydroxide, and the mass ratio thereof is 13:1. The chelating agent is prepared by mixing sodium hexametaphosphate and sodium polyacrylate, and the mass ratio thereof is 1:1.

[0075] The sludge biochar is prepared from municipal sludge, and the preparation method thereof comprises the following steps:

[0076] Step A1: Place the filter press sludge cake after removing a large amount of water through the filter press in a drying oven, dry at 105°C for 24 hours, and after preliminary crushing by a crusher, pass through a 150-mesh sieve to obtain dry sludge;

[0077] Step A2: Put the dry sludge into a granulator, add an appropriate amount of water, prepare sludge balls with a diameter of 1 cm, put them into a drying oven at 50°C for 5 hours, and obtain sludge balls;

[0078] Step A3: placing the sludge balls in a high-temperature tube furnace, controlling the heating rate to 5°C / min, pyrolyzing at 600°C for 2h under a nitrogen atmosphere, stopping heating, cooling to room temperature, and initially forming biochar;

[0079] Step A4: The biochar was repeatedly washed with deionized water to remove soluble impurities, and then dried at 105° C. for 7 h to obtain sludge biochar.

[0080] The preparation method of the carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent is prepared in the following manner:

[0081] B1: Red mud, regenerated micropowder and pore-forming agent were placed in a granulator and mixed for 4 min, then sludge biochar was added, and the granulator was operated for 2 min and mixed thoroughly to obtain a mixture;

[0082] B2: Divide the water into two parts, dissolve the activator and the chelating agent in different water respectively to obtain two additive solutions;

[0083] B3: Continuously spray two additive solutions for granulation to obtain spherical particles, which are then sieved to obtain ceramsite raw material balls with a particle size of 5-10 mm; during granulation, the speed of the granulator is 35 rpm, and the granulation is continuous for 6 minutes, during which the additive solution is evenly sprayed, and then the operation is continued for 2 minutes to compact the particles;

[0084] B4: The raw material balls are carbon cured for 1 day; the carbon curing conditions are: temperature 25±2℃, humidity 50%±2%, CO2 concentration 30%±2%;

[0085] B5: The cured particles are placed in water and cured for 28 days. The curing conditions are: temperature is 25±2°C, humidity is above 90%, and carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent is obtained.

[0086] Example 5

[0087] A carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent includes the following components in parts by weight: 60 parts of sludge biochar, 55 parts of red mud, 35 parts of regenerated micropowder, 15 parts of water, 2 parts of pore formers, 0 parts of activators, and 2 parts of chelating agents. The average particle size of the red mud and the regenerated micropowder is 20 μm, wherein the activity index of the regenerated micropowder is 0.73. The pore former is aluminum powder with a particle size of 0.5-2.0 μm. The chelating agent is prepared by mixing sodium hexametaphosphate and sodium polyacrylate, and the mass ratio is 1:1.

[0088] The sludge biochar is prepared from municipal sludge, and the preparation method thereof comprises the following steps:

[0089] Step A1: Place the filter press sludge cake after removing a large amount of water through the filter press in a drying oven, dry at 105°C for 24 hours, and after preliminary crushing by a crusher, pass through a 150-mesh sieve to obtain dry sludge;

[0090] Step A2: Put the dry sludge into a granulator, add an appropriate amount of water, prepare sludge balls with a diameter of 1 cm, put them into a drying oven at 50°C for 5 hours, and obtain sludge balls;

[0091] Step A3: placing the sludge balls in a high-temperature tube furnace, controlling the heating rate to 5°C / min, pyrolyzing at 400°C for 0.5h under a nitrogen atmosphere, then stopping heating and cooling to room temperature to initially form biochar;

[0092] Step A4: The biochar was repeatedly washed with deionized water to remove soluble impurities, and then dried at 105° C. for 6 h to obtain sludge biochar.

[0093] The preparation method of the carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent is prepared in the following manner:

[0094] B1: Red mud, regenerated micropowder and pore-forming agent were placed in a granulator and mixed for 3 min, then sludge biochar was added, and the granulator was operated for 2 min to fully mix and obtain a mixture;

[0095] B2: Divide the water into two parts, dissolve the activator and the chelating agent in different parts of water respectively, and obtain two additive solutions;

[0096] B3: Continuously spray two additive solutions to granulate, obtain spherical particles, and then screen to obtain ceramsite raw material balls with a particle size of 5-10mm; during granulation, the speed of the granulator is 30rpm, and the granulation is continuous for 12min, during which the additive solution is evenly sprayed, and then continue to run for 1min after the end to compact the particles;

[0097] B4: The raw material balls are carbon cured for 1 day; the carbon curing conditions are: temperature 25±2℃, humidity 50%±2%, CO2 concentration 20%±2%;

[0098] B5: The cured particles are placed in water and cured for 28 days. The curing conditions are: temperature is 25±2°C, humidity is above 90%, and carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent is obtained.

[0099] Example 6

[0100] The difference from Example 1 is that the preparation method of the carbon-cured red mud-regenerated micro-powder core-shell ceramsite adsorbent is as follows: Step B5 is cured for 3 days. The rest is the same as Example 1.

[0101] Example 7

[0102] The difference from Example 1 is that the preparation method of the carbon-cured red mud-regenerated micro-powder core-shell ceramsite adsorbent is as follows: Step B5 is cured for 7 days. The rest is the same as Example 1.

[0103] Example 8

[0104] The difference from Example 1 is that the preparation method of the carbon-cured red mud-regenerated micro-powder core-shell ceramsite adsorbent is as follows: Step B5 is cured for 14 days. The rest is the same as Example 1.

[0105] After preparation, they were tested in accordance with GB / T 17431.2-2010 “Lightweight aggregate and its test methods Part 2: Lightweight aggregate test methods”, and the results are shown in Table 1.

[0106] Table 1 Physical and mechanical properties test results of Examples 1-8

[0107]

[0108]

[0109] The carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent prepared in Examples 1-8 has good physical and mechanical properties. With the increase of red mud mass, the cylinder pressure strength of ceramsite decreases, while the bulk density increases and the 1h water absorption rate also increases. This shows that the increase of red mud makes the ceramsite denser, thereby affecting its mechanical properties and water resistance. Sodium hexametaphosphate and sodium polyacrylate, as chelating agents, have different effects on the performance of ceramsite. Sodium hexametaphosphate can more effectively stabilize heavy metals and improve the water resistance of ceramsite, while sodium polyacrylate helps to further improve the cylinder pressure strength of ceramsite.

[0110] In addition, the adsorption performance test of carbon-cured red mud-regenerated micro-powder core-shell ceramsite adsorbent was carried out. 50 mg / L Pb(NO3)2 solution, 50 mg / L CuCl2 solution and 50 mg / L KH2PO4 solution were prepared to simulate the sewage, and the mass ratio of ceramsite adsorbent: simulated solution = 1:20 was used. The ceramsite adsorbent was added and adsorbed at room temperature for 24 hours. The pollutant removal rate was measured. The results are shown in Table 2.

[0111] Table 2 Results of removal rates of various ions in Examples 1-8

[0112] Case <![CDATA[Pb 2+ (%)]]> <![CDATA[Cu 2+ (%)]]> <![CDATA[PO4 2- (%)]]> Example 1 82.33 80.51 93.22 Example 2 81.32 78.93 90.01 Example 3 79.10 78.82 91.76 Example 4 79.21 71.31 87.36 Example 5 76.84 76.34 85.68 Example 6 78.25 77.32 89.4 Example 7 80.24 78.11 90.73 Example 8 81.63 80..20 92.51

[0113] From the data in Table 2, it can be seen that the carbon-cured red mud-regenerated micro-powder core-shell ceramsite adsorbent prepared in Examples 1-8 has an adsorption capacity of Pb 2+ , Cu 2+ and PO4 2- The adsorption performance was significantly improved.

[0114] The above description is only a preferred specific implementation manner of the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.

Claims

1. A carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent, characterized in that: The raw materials include the following components in parts by weight: 60-100 parts of sludge biochar, 30-60 parts of red mud, 50-80 parts of regenerated micro powder, 10-20 parts of water, 2-5 parts of pore former, 0-5 parts of activator and 1-3 parts of chelating agent.

2. A carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent according to claim 1, characterized in that: The sludge biochar is prepared from municipal sludge, and the preparation method thereof comprises the following steps: Step A1: Place the filter press sludge cake after removing a large amount of water through the filter press in a drying oven, dry it at 105°C for 24 hours, and after preliminary crushing by a crusher, pass it through a 150-mesh sieve to obtain dry sludge; Step A2: Put the dry sludge into a granulator, add an appropriate amount of water, prepare sludge balls with a diameter of 1 cm, put them into a drying oven at 50°C for 5 hours, and obtain sludge balls; Step A3: placing the sludge balls in a high-temperature tube furnace, controlling the heating rate to 5°C / min, pyrolyzing at 400-600°C for 0.5-2h under a nitrogen atmosphere, then stopping heating and cooling to room temperature to initially form biochar; Step A4: The biochar is repeatedly washed with deionized water to remove soluble impurities, and then dried at 105° C. for 6-10 h to obtain sludge biochar.

3. The carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent according to claim 1, characterized in that: The average particle size of the red mud and the regenerated micro powder is 10-20 μm, wherein the activity index of the regenerated micro powder is greater than 0.

7.

4. The carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent according to claim 1, characterized in that: The pore-forming agent is aluminum powder with a particle size of 0.5-2.0 μm.

5. The carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent according to claim 1, characterized in that: The activator is prepared by mixing water glass and sodium hydroxide, and the mass ratio thereof is 10-15:

1.

6. The carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent according to claim 1, characterized in that: The chelating agent is prepared by mixing sodium hexametaphosphate and sodium polyacrylate, and the mass ratio thereof is 1:

1.

7. A method for preparing a carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent according to any one of claims 1 to 6, characterized in that: The following steps are involved: B1: Red mud, regenerated micropowder and pore-forming agent were placed in a granulator and mixed for 2-4 minutes, then sludge biochar was added, and the granulator was operated for 2 minutes to fully mix and obtain a mixture; B2: Divide the water into two parts, dissolve the activator and the chelating agent in different water respectively to obtain two additive solutions; B3: Continuously spray two additive solutions for granulation to obtain spherical particles, and then screen to obtain ceramsite raw material balls with a particle size of 5-10 mm; the rotation speed of the granulator is 30-40rpm, and the granulation is continuous for 6-12min, during which the additive solution is evenly sprayed, and then it is continued to run for 1-3min after the end to compact the particles; B4: Carbide-cured raw material balls for 1 day; the carbon curing conditions are: temperature of 25±2°C, humidity of 50%±2%, CO2 concentration of 20%±2%-40%±2%; B5: placing the carbon-cured particles in water and curing them for 3-28 days to obtain carbon-cured red mud-regenerated micropowder core-shell ceramsite adsorbent; the curing conditions are: temperature of 25±2° C. and humidity of more than 90%.

8. The carbon-cured red mud-regenerated micro-powder core-shell ceramsite adsorbent according to any one of claims 1 to 6 is used to remove Pb from water 2+ , Cu 2+ or PO4 2- Application in.

9. The use according to claim 8, characterized in that: At room temperature, the carbon-cured red mud-regenerated micro-powder core-shell ceramsite adsorbent is added at a mass ratio of 1:20 between the carbon-cured red mud-regenerated micro-powder core-shell ceramsite adsorbent and water.

Citation Information

Patent Citations

  • Sludge harmless treatment method and device thereof

    CN108689561A

  • Method for treating sludge and sewage by using modified red mud and modified steel slag

    CN113231012A

  • Sintering-free ceramsite and preparation method thereof

    CN114920530A

  • Core-shell biomass adsorbent and preparation method thereof

    CN114950365A

  • Preparation method of ceramsite adsorbent

    CN115970634A